2022
DOI: 10.1002/mnfr.202100355
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Effects of Royal Jelly on Estrogen‐ and Progesterone‐Induced Mammary Gland Hyperplasia in Rats

Abstract: Scope: Royal jelly (RJ) has a wide range of biological functions, its effect on hyperplasia of the mammary gland (HMG) in mammals is unclear. This study aims to investigate the effect of RJ on HMG and the dose-response relationship of RJ in the treatment of HMG. Methods and Results: HMG rats are induced by intramuscular injection of estrogen (E2) and progesterone, and are treated with different doses of RJ (100, 200, 400, and 800 mg kg -1 d -1 ). As a result, RJ improves the expansion of acinar and breast tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Unfortunately, the presence of other steroid hormones in RJ had not been assessed. Nevertheless, previous research has shown that RJ can significantly increase the levels of progesterone in rats and ewes [11,21]. When applied vaginally, RJ cream is more effective than estrogens in improving sexual and urinary function in postmenopausal women, suggesting a possible absorption of RJ components by the vaginal wall [22].…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, the presence of other steroid hormones in RJ had not been assessed. Nevertheless, previous research has shown that RJ can significantly increase the levels of progesterone in rats and ewes [11,21]. When applied vaginally, RJ cream is more effective than estrogens in improving sexual and urinary function in postmenopausal women, suggesting a possible absorption of RJ components by the vaginal wall [22].…”
Section: Discussionmentioning
confidence: 97%
“…Modern medicine also believes that the occurrence of MGH is linked to endocrine disorders, in particular, it is related to the imbalance of balance hypothalamic-pituitary-ovarian-mammary gland endocrine axis, in which the secretion of estrogen increases and the secretion of progesterone decreases. The imbalance of female/progesterone ratio is the main cause of mammary gland hyperplasia ( 38 41 ). The mammary gland is an important target organ for the effect of estrogen, and when estrogen secretion in the female organism is too high, it will cause the female breast tissue to be in a state of over-stimulation, and the poor physical condition will have an impact on the mammary gland, leading to MGH ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%